Exploring the Link between Financial Behavior, Financial Stress, and Online Loans among Urban Workers in Medan - Marlina, Marlina; Wahyuni, Sri; Helmi, Lika Akana (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
The rise of online loans and PayLater services in Indonesia has raised concerns about financial vulnerability, especially among middle-income earners. This study aims to examine the relationship between financial behavior, financial stress, and the risk of being entangled in online lending. Using a quantitative approach, data were collected through a questionnaire distributed to 100 respondents, predominantly teachers aged 31–45 with bachelor’s degrees. The analysis reveals a significant inverse relationship between financial behavior and financial stress, as well as between financial behavior and susceptibility to online loans. Key indicators such as budgeting, saving habits, and financial control were found to influence outcomes. Despite their stable income and educational background, many respondents lacked essential financial practices such as recording income and expenses, creating budgets, and building emergency funds. This highlights a behavioral gap between financial knowledge and application. The findings emphasize the need for targeted financial literacy programs that promote not only knowledge but also behavioral change. Strengthening responsible financial habits is essential to improving financial resilience and reducing dependence on high-risk digital credit platforms.